Impact of post-traumatic stress disorder symptoms, childhood adversities and stressful life events on depressive and anxiety symptoms: insights from the UK Biobank - Ma, Qianshu; Xie, Min; Llamocca, Elyse; Luo, Yupeng; Xiao, Liling; Tang, Yiguo; Tao, Shiwan; Wu, Yulu; Huang, Yunqi; Yin, Yubing; Liu, Yunjia; Liu, Siyi; et al. (Frontiers in Psychiatry, 2025)
BackgroundChildhood adversities (CAs) and stressful life events (SLEs) are linked to depressive, anxiety, and PTSD symptoms. However, their interrelationships are not well studied. We aimed to examine the potential role of PTSD symptoms as risk factors for both outcomes, test the stress sensitization hypothesis, and investigate the pathways linking CAs, stressful life events (SLEs) and PTSD symptoms, and depressive and anxiety symptoms.MethodsWe conducted a cross-sectional study using data from adult participants at baseline (2006-2010) and online follow-up (2016) in the UK Biobank. Data analysis was performed from February 24, 2023, to July 12, 2023. Linear regression and serial mediation analyses were performed.ResultsPTSD symptoms was significantly associated with depressive (β = 0.567, p<.001) and anxiety symptoms (β = 0.558, p<.001). The interaction between CAs and SLEs was still significantly associated with depressive symptoms when accounting for those of PTSD as covariates (β = 0.017, p<.001), but not for anxiety symptoms. The serial mediation analyses revealed that SLEs and PTSD symptoms were both significant sequential mediators between CAs and symptoms of depression and anxiety (proportion mediated: 75.14% and 84.27%, respectively, p< 0.05).ConclusionsOur study provided further evidence for stress sensitization hypothesis only among participants with depressive symptoms and found that SLEs and PSTD symptoms partly mediated the association between CAs and depressive and anxiety symptoms. These findings may provide new evidence to better understand the pathogenesis of depression and anxiety and will help to guide future prevention and intervention for both diseases.